Systematic Review and Meta-Analysis of the Clinical Evidence on the Use of Autologous Matrix-Induced Chondrogenesis in the Knee. (December 2021) - Steinwachs, Matthias R.; Gille, Justus; Volz, Martin; Anders, Sven; Jakob, Roland; De Girolamo, Laura; Volpi, Piero; Schiavone-Panni, Alfredo; Scheffler, Sven; Reiss, Eric; Wittmann, Udo
Objective: A systematic review and meta-analysis of Autologous Matrix-Induced Chondrogenesis (AMIC®) outcomes for grade III/IV chondral and osteochondral lesions of the knee treated with Chondro-Gide®. Design: Studies with a minimum follow-up of 1 year providing clinical results of AMIC repair in the knee were included based on PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Methodological quality was assessed by the modified Coleman Methodology Score (mCMS). The meta-analysis was comparing pain VAS (Visual Analog Scale), Lysholm score, and IKDC score (International Knee Documentation Committee) between baseline and follow-up after 1 or 2 years and after >3 years. Results: Twelve studies (375 patients) were included. The mCMS demonstrated a suboptimal study design (ranking between 52 and 80). The mean age was 36.2 years (14-70 years). The mean defect size was 4.24 cm 2 (0.8-22 cm 2 ). The results from the random effects model indicated a clinically significant ( P < 0.05) improvement of pain VAS from baseline to follow-up at year 1 to 2 of −4.02(confidence interval −4.37; −3.67), still significant after 3 years. Lysholm score at year 1 or 2 improved significantly and remained highly significant after 3 years. IKDC score showed highly significant improvement of 32.61 between 1 and 2 years versus baseline values maintained after 3 years. Conclusions: The AMIC procedure significantly improved the clinical status and functional scoring versus preoperative values. Evidence was obtained in a non-selected patient population, corresponding to real-life treatment of knee chondral and osteochondral defects. The evidence is sufficient to recommend AMIC in this indication.